EVELIO B. JAVIER: AWARENESS OF THE YOUNG GENERATION ABOUT THEIR LOCAL HERO (International Conference on Social and Islamic Studies, 2021)
Modern day heroes are rare. If there is one locally, this person will always be a study in contrast. With many people knowing and having made an interaction with the person it is expected that the person will be described in a way in which all his virtues and flaws will be given. This descriptive study sought to determine the level of awareness of the young generation about their local hero Evelio B. Javierand to develop learning materials about the life of the local hero Evelio B. Javier. The 526 respondents of the study in the level of awareness are the Grade 8 students from selected private and public secondary schools inthe Division of Antique randomly selected through stratified random sampling. Standard deviation and means were employed for the descriptive analysis of the study. The t-testand One-way ANOVA were used for inferential analysis. The respondents of the study exhibited a slight awareness level in terms of their knowledge about the life of Evelio B. Javier. When the respondents were grouped based on the schools where they were enrolled the three groups exhibited no significant difference on their means. This means that regardless of what school the students were enrolled the responses of the respondents will be statistically the same. Regardless of sex and school where they are enrolled, anybody can have the full potential to be aware of the life of the local hero Evelio B. Javier.